Hubungan Gangguan Neurobehavior dengan Paparan Pestisida pada Pekerja Perkebunan Teh PT X Kabupaten Cianjur - Zahra Salsabila Firdaus; Ismet Muchtar Nur (Jurnal Riset Kedokteran, 2021)
Abstract. Background: The use of pesticides in plantations or agriculture includes insecticides, herbicides, fungicides, rosenticides, and fumigants are chemicals from several groups, namely organochlorines, organophosphates, carbamates, and pyrethroids. Pesticides that are widely used in agriculture and plantations are the organophosphate group because this group is easier to decompose in nature. Besides being able to increase agricultural product yields, pesticides can also have a negative impact on workers in plantations due to exposure to pesticides, including nervous system disorders in the form of neurobehavioral disorders, which are harmful changes or functional disorders of the nerves, both the central nervous system and peripheral nervous system with symptoms / signs - a sign of changes in memory, attention, mood, disorientation, thinking irregularities, as well as changes in somatic, sensory, and cognitive function as neurotoxic effects due to the use of neurotoxicants. Aim: Research on workers in tea plantations aims to determine the relationship between neurobehavioral disorders in spraying workers (who use pesticides) in tea plantations. Method: This study used an observational analytic method which aims to reveal the correlative relationship between variables using a cross sectional group design approach and using a total sampling technique. The population and research sample amounted to 30. This study used a questionnaire The German Q18 Quesionnaire. The independent variable in this study is pesticides and the dependent variable in this study is neurobehavioral disorders. Univariate data analysis using frequency distribution and bivariate using chi-square. Result : The results showed that there was a relationship between the neurubehavioral disorders experienced by workers and the length of exposure to pesticides seen from their working period. The number of respondents who experienced neurobehavior disorders was 18 people (60.0%) had negative neurobehavioral disorders and as many as 12 people (40.0%) had positive neurobehavioral disorders. Chi-Square test results obtained p value = 0.011 <α (0.05), which means that there is a significant relationship / correlation between neurobehavioral disorders and exposure to pesticides in tea plantation workers of PT. X Cianjur Regency. Conclusion: in this study, there are neurobehavior disorders in plantation wprkers who use pesticides. Abstrak. Latar Belakang: Penggunaan pestisida dalam perkebunan atau pertanian meliputi insektisida, herbisida, fungisida, rosentisida, dan fumigan merupakan bahan kimia dari beberapa golongan yaitu organoklorin, organofosfat, karbamat, dan piretroid. Pestisida yang banyak digunakan di bidang pertanian dan perkebunan adalah golongan organofosfat karena golongan ini lebih mudah terurai di alam. Selain dapat meningkatkan hasil produk pertanian, pestisida juga dapat memberikan dampak negatif bagi pekerja di perkebunan akibat paparan pestisida, antara lain gangguan sistem saraf berupa gangguan neurobehavioral, yaitu perubahan berbahaya atau gangguan fungsional saraf, baik sistem saraf pusat dan sistem saraf tepi dengan gejala/tanda – tanda perubahan daya ingat, perhatian, mood, disorientasi, ketidakteraturan berpikir, serta perubahan fungsi somatik, sensorik, dan kognitif sebagai efek neurotoksik akibat penggunaan neurotoksikan. Tujuan: Penelitian pada pekerja di perkebunan teh bertujuan untuk mengetahui hubungan gangguan neurobehavioral pada pekerja penyemprotan (pengguna pestisida) di perkebunan teh. Metode: Penelitian ini menggunakan metode observasional analitik yang bertujuan untuk mengungkap hubungan korelasional antar variabel dengan menggunakan pendekatan cross sectional group design dan menggunakan teknik total sampling. Populasi dan sampel penelitian berjumlah 30. Penelitian ini menggunakan kuesioner The German Q18 Quesionnaire. Variabel bebas dalam penelitian ini adalah pestisida dan variabel terikat dalam penelitian ini adalah gangguan neurobehavioral. Analisis data univariat menggunakan distribusi frekuensi dan bivariat menggunakan chi-square. Hasil : Hasil penelitian menunjukkan bahwa ada hubungan antara gangguan neurobehavioral yang dialami pekerja dengan lama paparan pestisida dilihat dari masa kerjanya. Jumlah responden yang mengalami gangguan neurobehavior sebanyak 18 orang (60,0%) mengalami gangguan neurobehavior negatif dan sebanyak 12 orang (40,0%) mengalami gangguan neurobehavior positif. Hasil uji Chi-Square diperoleh p value = 0,011 < (0,05), yang berarti terdapat hubungan/korelasi yang signifikan antara gangguan neurobehavioral dengan paparan pestisida pada pekerja perkebunan teh PT. X Kabupaten Cianjur. Kesimpulan: pada penelitian ini terdapat gangguan neurobehavior pada pekerja perkebunan yang menggunakan pestisida.